Appoptosin Mediates Lesions Induced by Oxidative Stress Through the JNK-FoxO1 Pathway - Zhang, Cuilin; Tan, Zhenqiu; Xie, Yongzhuang; Zhao, Yingjun; Huang, Timothy Y.; Lu, Zhaoping; Luo, Hong; Can, Dan; Xu, Huaxi; Zhang, Yun-wu; Zhang, Xian (Frontiers in Aging Neuroscience, 2019)
Oxidative stress is a common feature of neurodegenerative diseases and plays an important role in disease progression. Appoptosin is a pro-apoptotic protein that contributes to the pathogenesis of neurodegenerative diseases such as Alzheimer’s disease and progressive supranuclear palsy. However, whether appoptosin mediates oxidative stress-induced neurotoxicity has yet to be determined. Here, we observe that appoptosin protein levels are induced by hydrogen peroxide (H2O2) exposure through the inhibition of proteasomal appoptosin degradation. Furthermore, we demonstrate that overexpression of appoptosin induces apoptosis through the JNK-FoxO1 pathway. Importantly, knockdown of appoptosin can ameliorate H2O2-induced JNK activation and apoptosis in primary neurons. Thus, we propose that appoptosin functions as an upstream regulator of the JNK-FoxO1 pathway, contributing to cell death in response to oxidative stress during neurodegeneration.